EFEKTIVITAS BUNGA WIJAYA KUSUMA (Epiphyllum oxypetalum) TERHADAP PENURUNAN KADAR ASAM URAT TIKUS WISTAR - rahayu artini yuan (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2019)
ABSTRACT            The isolation of wijaya kusuma (Epiphyllum oxypetalum) flower was carried out in this study. Methanol was applied to maceration an  27 g sample of extract its was produced from 250 g of sample powder. In vivo test results, methanol extract of wijaya kusuma flower (Epiphyllum oxypetalum) dose of 100 mg / kg BB, 200 mg / kg BB, and 400 mg / kg BW can decreasing uric acid concentration. From this research, it was obtained that the best dose of extract of wijaya kusuma flower (Epiphyllum oxypetalum) applied to decrease uric acid was 400 mg/Kg BW with a decrease percentage of 63,50%. The probit test results obtained the value of ED50 methanol extract of wijaya kusuma flower (Epiphyllum oxypetalum) of 221 mg / Kg BB. In this study it can be concluded that soursop leaf extract (Annona muricata L.) can reduce uric acid levels in research mice. For future research, this method could be applied to human in decreasing uric acid concentration in blood.Keywords: kusuma wijaya flower (Epiphyllum oxypetalum), extraction, maceration, and uric acid.